Private sector contributions and their effect on physician emigration in the developing world - Lawrence C Loh; Cesar Ugarte-Gil; Kwame Darko (The World Health Organization, 2013)
The contribution made by the private sector to health care in a low- or middle-income country may affect levels of physician emigration from that country. The increasing importance of the private sector in health care in the developing world has resulted in newfound academic interest in that sector's influences on many aspects of national health systems. The growth in physician emigration from the developing world has led to several attempts to identify both the factors that cause physicians to emigrate and the effects of physician emigration on primary care and population health in the countries that the physicians leave. When the relevant data on the emerging economies of Ghana, India and Peru were investigated, it appeared that the proportion of physicians participating in private health-care delivery, the percentage of health-care costs financed publicly and the amount of private health-care financing per capita were each inversely related to the level of physician expatriation. It therefore appears that private health-care delivery and financing may decrease physician emigration. There is clearly a need for similar research in other low- and middle-income countries, and for studies to see if, at the country level, temporal trends in the contribution made to health care by the private sector can be related to the corresponding trends in physician emigration. The ways in which private health care may be associated with access problems for the poor and therefore reduced equity also merit further investigation. The results should be of interest to policy-makers who aim to improve health systems worldwide.